AIDS, poverty, and hunger: challenges and responses - Gillespie, Stuart (International Food Policy Research Institute, 2006)
In a report written by international experts in agricultural economics, health, anthropology, and nutrition...the authors examine the impacts of HIV and AIDS on labor markets and wages, household income and consumption dynamics, and on the agricultural sector as a whole; analyze the ways in which households respond to prime-age illness, death, and food insecurity; and study the implications of such local responses for the roles of national and international actors in addressing the AIDS-hunger nexus.